Changing Architecture and Construction Practices in the Gilgit Baltistan Region, Pakistan: Case of Hotel and Tourism Industry - Hira Ovais; Maria Sajid Zaheer; Faryal Sikandar; Syed Asim Mobin; Bushra Danish Talpur (Sir Syed University Research Journal of Engineering and Technology)
The tourism and hotel industry is rapidly causing the alteration of the architectural and construction practices in the Gilgit-Baltistan region as more and more people have become associated with the industry including both the locals as well as outsiders. This paper presents an overview of the changing scenario of architecture and construction practices in the Gilgit-Baltistan region and the preferences of the local population. It aims to do so by highlighting the architectural and construction practices of the past and present specifically in the hotel and tourism industry of the region, outlining the type of construction and their techniques while also inquiring the locals regarding their preferences pertaining to architecture and construction. The secondary data giving an overview of the region, and the architectural and construction practices; is gathered from the relevant newspaper articles, reports, websites and, journal articles while the primary data is gathered from the site visits to the region along with questionnaire surveys conducted from the local population. An assessment of hotels developed during different timelines presenting case studies employing either vernacular or modern or even a combination of both techniques is carried out in terms of their use of materials, architectural features, and structure/construction typology. Conclusively, the research tries to put forth the trends in architecture and construction practices especially in the case of hotel buildings in the region as while an increase in tourism has caused a boost in the construction of hotels in the region, it has raised many other concerns such as disconnect from local culture, use of alienated building materials making the buildings poor in terms of thermal comfort, dying cultural heritage.